INNOVATION IN THE PUBLIC SECTOR: DIMENSIONS, PROCESSES, BARRIERS AND DEVELOPING A FOSTERING FRAMEWORK. - Simon P Taylor (International Journal of Research Science and Management, 2018)
Innovation in the public sector is an area that is being looked at by governments across the world to provide solutions to enable the delivery of services to customers. This is against a background of rising expectations, financial constraint as well as changing social, environmental and economic conditions. The pressures that governments across the world face to continue to find new ways of delivering public services has heightened the quest for innovation to be identified, applied and embedded in service delivery [1].